Foreign Aid Allocation, Governance, and Economic Growth - Akramov, Kamil (Book collections on Project MUSE., 2012)
Kamiljon T. Akramov investigates the effectiveness of foreign aid to developing countries by comparing the results of aid allocated to a recipient's production sectors, economic infrastructure, or social sectors.